Games and Sloth: Working for the Common Good in Late Medieval Flanders - Brown A (Oxford University Press, 2021)
Games, sloth and the common good are familiar subjects to scholars of late medieval Europe, yet the connections contemporaries made between them have never been properly explored. How these rhetorical ideas were aligned, how they were used and by whom, across a wide social spectrum, are the central questions in this article; and examining them reveals how malleable (and gendered) they were. Discourses on games, developed by schoolmen and other churchmen in relation to recreation, and integrated with ideas of sloth and the common good, were harnessed to serve the authority of rulers in late medieval Flanders and Burgundian lands. Yet they were also deployed to suit other agendas, especially during the troubled period of civil war from 1477 to 1492, by the rulers’ subjects—urban magistrates, elite or middling groups, but also men from lower social strata. Valuable evidence for the latter appears within the numerous pardon letters that survive from 1386 to 1500: these were specially granted by rulers to suppliants, many of whom were craftsmen, labourers and artisans. Suppliants often referred to their game-playing and recreational activities; while these cases suggest a process by which subjects were disciplined, they also show how discourses on games offered suppliants strategic room for manoeuvre.